Testing the effects of 4-week training programs based on extreme and medium-sided soccer games: a study focusing on change-of-direction, vertical jump height and locomotor profile - Piotr Makar; Gibson Praça; Adam Kawczyński; Zeki Akyildiz; Mehmet yıldız; Rodrigo Aquino; Filipe Manuel Clemente (BMC, 2022)
Abstract Aim This study tested the effects of two training programs (one program based on extreme sided-games of 1v1 vs. one program based on the medium-sided game of 5v5) on the physical fitness adaptations of youth soccer players. In specific, it was analyzed the effects of the training programs on the 5-0-5 change-of-direction time (5-0-5 time), countermovement jump (CMJ), and final velocity in the 30-15 Intermittent Fitness test (VIFT). Methods This study followed a randomized parallel study design. Twenty male regional-level soccer players (age: 17.0 ± 0.3 years old) were randomly assigned to two groups: (1) the 1v1 format; and (2) the 5v5 format. The training intervention lasted four weeks. The week before (baseline) and the week after the intervention, the participants were assessed in the 5-0-5 change-of-direction test (measured using timing gates), CMJ (measured by photoelectric cells), and 30-15 Intermittent Fitness test. The training intervention consisted of 8 sessions (2 sessions per week). The 1v1 group performed four repetitions of 30 s in each session, while the 5v5 group performed four repetitions of 4 min. Results The 5-0-5 time changed − 4.82% (p = 0.004; d = 1.115) for the 1v1 group and − 4.26% (p = 0.004; d = 0.859) for the 5v5 group. CMJ changes occurred both in the 1v1 and 5v5 group and amounted to 1.7% (p = 0.003; d = 0.509) and 1.2% (p = 0.263; d = 0.155) respectively. VIFT changed 2.6% (p = 0.718; d = 0.178) for the 1v1 group and 3.0% (p = 0.593; d = 0.274) for the 5v5 group. The 1v1 group reported significantly lower post-intervention 5-0-5 time than the 5v5 group (− 4.3%; p = 0.048; d = 0.954), although no significant differences in CMJ (3.2%; p = 0.147; d = 0.678) and VIFT (2.5%; p = 0.697; d = 0.177) were revealed. Conclusions The extreme-sided games meaningfully beneficiated the vertical jump height and change-of-direction performance of youth soccer players. The extreme-sided games seem more beneficial than medium-sided games for improving these physical abilities while showing that four weeks were enough to impact the players significantly.